Diagnoza statusów tożsamości w okresie adolescencji, wyłaniającej się dorosłości i wczesnej dorosłości za pomocą Skali Wymiarów Rozwoju Tożsamości (DIDS) - Brzezińska, Anna Izabela; Piotrowski, Konrad (My University, 2009)
The paper presents the results of a research into the formation of identity statuses during the periods of adolescence, emerging adulthood and early adulthood. 711 individuals participated in the study, from 4 age groups: 14 to 17, 18 to 23, 24 to 29 and 30 to 40 years old. The results indicate that in the first two age groups the process of exploration is dominant, while participants from the latter two age groups focus on making commitments and identifying with them. Regardless of the age group, the status of diffused identity was rarely seen, as was the status of foreclosed identity in the groups below the age of 24. Also, the older the group, the lower the percentage of individuals with the ruminative moratorium identity status. The statuses of undifferentiated and achieved identity occurred with similar frequency in all age groups with the exception of 18-to-23-year-olds, i.e. full-time college students. In this group the status of achieved identity occurred less frequently than in the other age groups, while the reverse was true for undifferentiated identity.
A diagnosis of identity status in adolescence, emerging adulthood and early adulthood using the Dimensions of Identity Development Scale (DIDS)
Artykuł prezentuje wyniki badań nad formowaniem się statusu tożsamości wśród osób w okresie adolescencji, wyłaniającej się dorosłości i wczesnej dorosłości. W badaniach wzięło udział 711 osób, należących do 4 grup wiekowych: 14 - 17 lat, 18 - 23 lata, 24 - 29 lat oraz 30 - 40 lat. Wyniki ujawniły, iż w przypadku dwóch młodszych grup wiekowych dominuje proces eksploracji, osoby z dwóch kolejnych grup są bardziej skoncentrowane na podejmowaniu i identyfikowaniu się z zobowiązaniami. Niezależnie od grupy wiekowej, stosunkowo rzadko pojawia się status tożsamości rozproszonej, a wśród osób do 24 roku życia także status tożsamości przejętej. W kolejnych grupach wiekowych coraz mniejszy odsetek osób posiada status tożsamości ruminacyjno-moratoryjnej. Częstość występowania statusu tożsamości niezróżnicowanej oraz tożsamości osiągniętej jest podobna we wszystkich grupach wiekowych, z wyjątkiem grupy 18 - 23-latków, czyli studentów studiów stacjonarnych. W tej grupie status tożsamości osiągniętej występuje rzadziej, a tożsamości niezróżnicowanej częściej niż w pozostałych grupach.